To compose a number is to compose a cardinality: evidence from intensional contexts - Alonso-Ovalle, Luis; Schwarz, Bernhard (Proceedings of the Amsterdam Colloquium, 2024)
DPs of the form the number of NP can combine with predicates of numbers or with predicates of ordinary entities. The interpretation of such DPs in intensional contexts favours an account of this flexibility based on syntactic ambiguity (Alonso-Ovalle and Schwarz 2024) over an account based on constructing numbers from ordinary entities (cf. Scontras 2017).